Plasma activated water (PAW): Chemistry, physico-chemical properties, applications in food and agriculture. (July 2018) - Thirumdas, Rohit; Kothakota, Anjinelyulu; Annapure, Uday; Siliveru, Kaliramesh; Blundell, Renald; Gatt, Ruben; Valdramidis, Vasilis P.
Abstract: Background: Cold plasma is an emerging non-thermal disinfection and surface modification technology which is chemical free, and eco-friendly. Plasma treatment of water, termed as plasma activated water (PAW), creates an acidic environment which results in changes of the redox potential, conductivity and in the formation of reactive oxygen (ROS) and nitrogen species (RNS). As a result, PAW has different chemical composition than water and can serve as an alternative method for microbial disinfection. Scope and approach: This paper reviews the different plasma sources employed for PAW generation, its physico-chemical properties and potential areas of PAW applications. More specifically, the physical and chemical properties of PAW are outlined in relation to the acidity, conductivity, redox potential, and concentration of ROS, RNS in the treated water. All these effects are in microbial nature, so the applications of PAW for microbial disinfection are also summarized in this review. Finally, the role of PAW in improving the agricultural practices, for example, promoting seed germination and plant growth, is also presented. Key findings and conclusions: PAW appears to have a synergistic effect on the disinfection of food while it can also promote seedling growth of seeds. The increase in the nitrate and nitrite ions in the PAW could be the main reason for the increase in plant growth. Soaking seeds in PAW not only serves as an anti-bacterial but also enhances the seed germination and plant growth. PAW could potentially be used to increase crop yield and to fight against the drought stress environmental conditions. Highlights: PAW is easy to apply replacing the traditional sanitizing solutions. Synergistic effect of acidification of water and reactive species is evident in PAW. Nitrate of PAW absorbed through the roots act as plant growth enhancers. Active species of PAW contribute to seed germination enhancement. PAW has the ability to inhibit the hormones responsible for seed dormancy.